Implementasi Pendidikan Karakter dalam Kurikulum 2013 - Kaimuddin, Kaimuddin (IAIN Samarinda, 2014)
The implementation of character education in formal educational environments have effective influence in addressing the phenomenon of anarchism, the imposition of the will, brawl learners, the proliferation of drug dealers and users, environmental crisis, a moral crisis, and various other social fatologi tendencies. Formal education is an education system that is organized, purposeful, and measurable. Curriculum 2013 orientates and emphasizes on the strengthening of the moral, affective, and value of the concept of KI-1 (spiritual attitude), KI-2 (social attitudes), KI-3 (knowledge), and KI-4 (application of knowledge). Implementation of character education in the Curriculum in 2013 can be developed by integrating cognitive, affective, and psycho-motoric aspects. In addition, to encourage and facilitate the realization of synergies between formal, non-formal and informal education, and encourage teachers to continue to improve the competence and their role model is another form of implementation of Curriculum 2013.